Az Egészségegyenlőtlenségek néhány összefüggése a társadalmi-gazdasági egyenlőtlenségekkel Magyarországon - Egri Zoltán; Uzzoli Annamária („RIK-U” Kft., 2020)
Abstract. Socio-economic environment can influence many aspects of health and access to health care is one of them. This study hypothesized that socio-economically disadvantaged neighbourhoods tend to have relatively poor access to health care which can result in significant health inequalities in Hungary. Our results are based on using quantitative method of ESDA (Explanatory Spatial Data Analysis) to examine spatial distribution of one of non-communicable diseases such as acute myocardial infarction regarding its accessibility.
Health inequalities and some of their connections with socio-economic inequalities in Hungary
https://kmf.uz.ua/wp-content/uploads/2020/09/final_1_kotet-foldrajzfkonf-2020-07-14.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00008119
Keywords: health inequality; accessibility; acute myocardial infarction; Hungary